2022
DOI: 10.1371/journal.pone.0273659
|View full text |Cite
|
Sign up to set email alerts
|

Functional disability among older adults in India; a gender perspective

Abstract: Introduction Older adults are always at a greater risk of physical and functional health challenges. These complications result into morbidity, disability and death making them more vulnerable at later ages. Therefore, this paper will examine the functional health status among older adults and its gender perspective, along with associated risk factors. Materials and methods Using the first round of Longitudinal ageing survey of India (2017–18). Functional disability was computed based on general and instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Similar to our findings, multiple authors have reported that the presence of chronic illness increases the probability of activity limitation, thus increasing the dependency. [ 25 26 ] Given the enormous influence of morbidity on functional disability, an urgent need arises t reduce the likelihood of chronic diseases by improving the access to health-care services and financing among the elderly in India. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, multiple authors have reported that the presence of chronic illness increases the probability of activity limitation, thus increasing the dependency. [ 25 26 ] Given the enormous influence of morbidity on functional disability, an urgent need arises t reduce the likelihood of chronic diseases by improving the access to health-care services and financing among the elderly in India. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Further research and interventions focused on CVD should consider employing functional health screenings to potentially disrupt or mitigate functional decline that could render some older adults, especially men, more susceptible to mental distress. This is especially important given the otherwise well-documented finding that a greater proportion of women than men face functional disability in later life [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The variation in findings could be attributed to the specific socioeconomic and environmental contexts of the study populations. Factors such as access to healthcare services, living conditions, and socioeconomic disparities may contribute to the disparities in functional difficulty observed in different populations (Bora & Saikia, 2015;Ćwirlej-Sozańska et al, 2019;Dunlop et al, 2002;Malik, 2022).…”
Section: Functional Difficultiesmentioning
confidence: 99%
“…These findings suggest that advancing age may contribute to an increased likelihood of experiencing functional difficulties. Factors such as declining physical health, age-related chronic conditions and reduced mobility and flexibility could potentially explain the higher prevalence of functional difficulty in older women (Dunlop et al, 2002;Malik, 2022).…”
Section: Functional Difficultiesmentioning
confidence: 99%